A general framework for predicting the ecological effects of range expansions in marine systems - Ryan A. Beshai; Cascade J. B. Sorte (Proceedings of the National Academy of Sciences, 2026)
Warming global temperatures are driving species to shift beyond their historical geographic ranges into novel, expanded ranges, where they may have both positive and negative effects on recipient populations. Although no framework currently exists to anticipate these effects, invasion biology theory suggests expanders’ effects may be predictable from expanders’ historical roles and trophic positions. We conducted a global synthesis of over 1,200 population-level effects of marine range-expanding species reported across 1,075 studies. We hypothesized that, similar to invasive species, expanding species’ impacts could be predicted by (H1) their ecological roles in their historical ranges and (H2) their trophic levels. We found that effects in these species’ historical ranges reliably predict their impacts in expanded ranges, but that, overall, marine range expanders tend to be more detrimental—or less beneficial—in novel communities. Higher trophic level expanders tend to have stronger effects (both positive and negative) on resident species than lower trophic level expanders. Effect magnitudes were further modulated by the type of interaction (e.g., predation, competition, physical disturbance, etc.), with the strongest effects arising from indirect interactions. Finally, we found that native producers experienced some of the strongest effects when compared to humans, vertebrates, or invertebrates. Together, our results indicate that existing knowledge of species’ roles are key to anticipating which climate-driven range expansions are likely to have the largest effects on recipient communities.